Migration and climate change from prehistoric cultures to contemporary management in organizations - Alaktif, Jamila (ISTE, Ltd. ; Wiley, 2020)
This book aims to provide a better understanding of how human cultures interact with climate change over an extended period of time. It is an analysis of the past and present, ranging from the first human migration to contemporary organizational management using an approach developed by Michel Foucault, defined as: the research, the practice, the experience, by which the subject operates on themselves the transformations necessary in order to have access to the truth. This book consists of two parts. The first part focuses on climate change and the substantial effects it had on the first human cultures. The second part explores the role of organizations and the development of new frameworks for action in more recent times of anthropogenic climate change.